Investigating the accessibility and impacts of cybersecurity programs on high-school girls' long-term industry engagement. (29th October 2021) - Shan, Mridula; Yang, Jeong
Abstract : Purpose: The purpose of this study is to investigate whether having accessible cybersecurity programs (CPs) for high-school students affected girls' long-term engagement with the industry, given that they already had interests in technology. Although much research has been done to evaluate how high-school science, technology, engineering, and mathematics programs retain girls in computing fields, it is necessary to see if this same long-term engagement exists in cybersecurity-specific programs. Design/methodology/approach: In total, 55 members were surveyed from the aspirations in computing community regarding their experience in and accessibility to high-school CPs. A quantitative analysis of such responses was then undertaken using inferential statistical tools and chi-squared tests for independence. Findings: The results showed that the existence of CPs alone are not influential factors in increasing long-term engagement with the field, showcasing that the high-knowledge barrier of CPs affects many students (even those with prior interests in technology). Instead, by having multiple occurrences of these programs and providing more cybersecurity resources to areas that lacked them, girls were more likely to report an increased interest in the field. Practical implications: Such information can support future program leaders to develop effective, accessible and more targeted cybersecurity initiatives for students of various communities. Originality/value: By analyzing the unique interactions of tech-aspiring women with cybersecurity, this exploration was able to demonstrate that women of different computing experiences face a shared barrier when entering the cybersecurity field. Likewise, in comparing these perspectives across different age groups, the investigation highlighted the development and subsequent growth of cybersecurity programming over the years and why such initiatives should be supported into the future.